Síntese, caracterização, propriedades e aplicação dos sistemas Mg- Al, Zn-Al e Mg-Fe - Hora, Paulo Henrique Almeida da (2014)
The Layered Double Hydroxides has become extremely promising materials due to its range of applications, easily obtained in the laboratory and reusability after calcination, so the knowledge regarding their properties is of utmost importance. In this study were synthesized layered double hydroxides of two systems, Mg-Al and Zn-Al, and such materials were analyzed with X-ray diffraction and, from these data, we determined the volume density, planar atomic density, size crystallite, lattice parameters, interplanar spacing and interlayer space available. Such materials were also subjected to thermogravimetric analysis reasons for heating 5, 10, 20 and 25 ° C / min to determine kinetic parameters for the formation of metaphases HTD and HTB based on theoretical models Ozawa, Flynn-Wall Starink and Model Free Kinetics. In addition, the layered double hydroxides synthesized in this working ratios were calcined heating 2.5 ° C / min and 20 ° C / min, and tested for adsorption of nitrate anion in aqueous solution batch system at time intervals 5 min, 15 min, 30 min, 1h, 2h and 4h. Such calcined materials were also subjected to exposure to the atmosphere and at intervals of 1 week, 2 weeks and 1 month were analyzed by infrared spectroscopy to study the kinetics of regeneration determining structural called "memory effect"